Salting-out assisted liquid-liquid extraction coupled with hydrophilic interaction chromatography for the determination of biguanides in biological and environmental samples - Alshishani, A. (Elsevier B.V., 2018)
A new salting-out assisted liquid-liquid extraction (SALLE) sample preparation method for the determination of the polar anti-diabetic biguanide drugs (metformin, buformin and phenformin) in blood plasma, urine and lake water samples were developed. The SALLE was performed by mixing samples (plasma (0.2 mL), urine or lake water (1.0 mL)) with acetonitrile (0.4 mL for plasma, 0.5 mL for urine or lake water), sodium hydroxide powder was then added for the phase separation. The effects of type of salting-out reagent, type of extraction solvent, volumes of acetonitrile and sample, amount of sodium hydroxide, vortexing and centrifugation times on the extraction efficiency were investigated. The upper layer, containing the biguanides, was directly injected into a HPLC unit using ZIC-HILIC column (150 mm Ã 2.1 mm Ã 3.5 Î¼m) and was detected at 236 nm. The method was validated and calibration curves were linear with r2 > 0.99 over the range of 20â2000 Î¼g Lâ1 for plasma and 5â2000 Î¼g Lâ1 for urine and lake water samples. The limits of detection were in the range (3.8â5.6) Î¼g Lâ1, (0.8â1.5) Î¼g Lâ1 and (0.3â0.8) Î¼g Lâ1 for plasma, urine and lake water, respectively. The accuracies in the three matrices were within 87.3â103, 87.4â109, 82.2â109 of the nominal concentration for metformin, buformin and phenformin, respectively. The relative standard deviation for inter- and intra âday precision were in the range of 1.0â17 for all analytes in the three matrices. Â© 2017 Elsevier B.V.